안면 형태학적 특성과 성격 특성 사이의 연관성에 대한 탐색 연구 - 백영화(Young Hwa Baek); 김상혁(Sang Hyuk Kim); 도준형(Jun Hyeong Do); 박기현(Ki Hyun Park); 장은수(Eun Su Jang) (동의생리병리학회지, 2012)
There have been many studies to find out association between the face characteristics and some diseases or the personality and the health state, but there have been few association studies between the face characteristics and the yin/yang personality. We would like to suggest that the yin/yang personality is associated with the face characteristics. We collected 1,471 subjects from the February, 2008 to July, 2010. We divided into three groups of subjects by a yin/yang personality score and analyzed the face characteristics after adjusting for age. The Analysis of Covariance and Scheffe test was conducted to certify the difference among three groups. P-value for significance was under 0.05. The significant face characteristics were SH36 in men, and FD50_51, SH36, FArea04, FAreaRatio4, FR01, FR05 in women. There is some association between the face characteristics and the yin/yang personality.